Active Vibration Suppression of Nonlinear Cantilever Beam using Shape Memory Alloy Actuators. Issue 1 (2018) - Vishal, Prateek; Kaliperumal, Dhanalakshmi; Padhi, Radhakant
Abstract: This paper presents the active vibration suppression of a cantilever beam using shape memory alloy (SMA) wires as actuator. The cantilever beam is modelled as a nonlinear distributed parameter system (DPS) following the Euler Bernoulli Beam theory. Sensors and actuators are optimally placed at discrete locations along the cantilever beam. Controllability Gramians are evaluated to determine the optimal locations for the actuator placement. Modal analysis is used to determine the optimal locations for the sensor placement. The desired system response is obtained by designing a nonlinear controller using the concepts of dynamic inversion and optimal control. This methodology is based on the Design Then Approximate (DTA) philosophy. Optimal Dynamic Inversion is used as the control technique to ensure suppression of vibration along the length of the beam. This approach of control design can be used for any randomly generated initial profile of the beam. Experimental setup is designed using discrete sensors such as LASER sensor and Piezoelectric Sensor and the actuation is done using SMA based wire actuators. The control algorithm is verified experimentally and theoretically for vibration suppression.